The Perspectives of Healthcare Professionals on the Strategies, Challenges, and Community Responses to Health System Response and Interventions Towards Lassa Fever Infections and Mortality in Sierra Leone - Kamara ABS; Fatoma P; Moseray A (Dove Medical Press, 2024)
Abu-Bakarr Steven Kamara, Patrick Fatoma, Andrew Moseray Department of Public Health, School of Community Health Sciences, Njala University Bo Campus, Bo City, Sierra LeoneCorrespondence: Abu-Bakarr Steven Kamara, Department of Public Health, School of Community Health Sciences, Njala University Bo Campus, Bo City, Sierra Leone, Tel +23276201595, Email abskamara@njala.edu.slBackground: Lassa fever is a critical public health issue in Sierra Leone that demands appropriate health system responses and interventions to mitigate infections and reduce mortality.Methods: A qualitative study was conducted to delve into healthcare workers' experiences with Lassa fever management and interventions across diverse healthcare settings in Sierra Leone, including the Eastern Province and Freetown's Directorate of Health Security and Emergency (DHSE). Engaging ten key informants through purposive sampling, the study employed NVivo version 10 for a detailed thematic analysis using Query and Coding to systematically identify, classify, and organize key themes regarding knowledge, diagnostics, management roles, and community impact.Results: The findings indicate a well-informed healthcare workforce but highlight gaps in early detection, diagnostic accuracy, and procedural standardization. Concerns were raised about the potential overestimation of disease incidence due to improved diagnostics, suggesting a historical under-detection of Lassa fever. The analysis underscores the need for a multifaceted management approach, emphasizing international collaboration and culturally sensitive community engagement to effectively tackle the disease. A significant concern identified is the high mortality rate resulting from delayed referrals and communication challenges within the health system, leading to actionable recommendations for enhancing Lassa fever response strategies. The study's thematic analysis provides a nuanced understanding of the challenges and areas for improvement, emphasizing the critical role of healthcare professionals in combating Lassa fever.Conclusion: Combating Lassa fever in Sierra Leone demands an integrative strategy that extends beyond medical interventions to encompass educational and infrastructural enhancements. This research pays homage to the commitment of healthcare professionals, underscoring the importance of sustained support and recognition of their essential contributions to advancing Lassa fever management and interventions.Keywords: Lassa fever, Sierra Leone, healthcare professionals, health system response, community engagement, diagnostic challenges, mortality, communication strategies